Effect of weight and size of seed on Moringa and Ricinus seedlings - Valdés-Rodríguez, Ofelia Andrea; Pérez-Vázquez, Arturo; Muñoz-Gamboa, Caupolicán (Revista Mexicana de Ciencias Agrícolas, 2018)
Ricinus communis L. and Moringa oleifera Lam. they are oleaginous with industrial applications that are promoted in poor soils. However, little is known about the relationship between weights and sizes of their seeds and their propagation in these media. So an investigation on these factors will allow to determine their real establishment capacities. The objectives of this study were to determine the relationship between weight and size of seeds of Ricinus and Moringa against germination and seedling growth. The 80 seeds per species were randomly selected. The seeds were weighed and measured and germinated in a sandy substrate. During two months, the number of days to germinate, stem height and diameter, leaf area, robustness index and final biomass were evaluated by correlation and regression analysis with seed sizes and weights. The results for both species showed shorter germination times in lighter seeds (r= -0.27 for Ricinus and -0.08 for Moringa), but also showed a positive correlation between weights and growth variables, being higher in stems (r= 0.41 for Ricinus and 0.68 for Moringa) and for the biomass of the stems (r= 0.35 for Ricinus and 0.53 for Moringa) and the roots. The length of the seed obtained the highest correlation in stem elongation for Ricinus (r= 0.24), while in Moringa it was the width (r= 0.61). It is concluded that heavier and larger seeds will produce taller seedlings with more profuse roots in a sandy substrate.